The subcellular localization of Eucalyptus grandis sucrose synthase 1 (EgSUSY1) fusion proteins expressed in Arabidopsis thaliana - Berger, David Kenneth (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.